Climate mobilities, rights and justice: Complexities and particularities - Farbotko, Carol; Thornton, Fanny; Mayrhofer, Monika; Hermann, Elfriede (Frontiers in Climate, 2022)
Climate mobility revolves around issues of justice and human rights, whether this be concerning its causes, expression or handling. This paper examines the justice-rights nexus as it relates to human mobility, highlighting how the two spheres converge and diverge. It works with four case studies exploring the complexity of rights and justice in the climate mobility context. Our case studies are diverse, in terms of the mobility types concerned and the rights and justice-based issues involved. We show that conceptualizing or achieving just or righteous outcomes is neither certain nor a uniform pursuit when it comes to climate mobility. Rather, there are many divergences – by those who claim rights or justice, and those asked to respond. We present a complex and contested space, highlight the importance of approaching justice and rights matters contextually, and with special attention to particularities when climate mobility is at issue.